Priority inclusive practices to improve paralympians` self-regulation abilities - Baranov, A. A.; Ovechkin, V. P.; Suntsova, A. S. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to rate benefits of the new mental training and inclusive practices to improve the Paralympians` self-regulation abilities. The elite Paralympians with musculoskeletal system impairments qualified for the Russian national skiing and biathlon teams were sampled for the study purposes. The new inclusive training model piloting experiment was designed to offer a combined mental control training (autogenic trainings, suggested relaxation, mental conditioning plus visual-auditory stimulations) and inclusive practices with meetings of the Paralympians, university students and schoolchildren. The sample was tested by the computerized Bio-Well Test System to rate the energy resource and background stress levels; and MINDSKIN Test System to rate the mental/ emotional stress levels by the galvanic skin response (GSR) tests. The study data and analyses showed benefits of the new mental conditioning inclusive practices as verified by the group progress in the mental and physical control abilities; shooting accuracy in biathlon subgroup; and the growing appreciation of the inclusive practices by the group recognizing their socializing, motivational and mental control improvement effects for the athletes with health impairments. We recommend the inclusive practices as a promising resource for the Paralympic sports facilitation purposes that needs to be addressed by further research.